Analisis Keberlanjutan Usahatani Sagu di Kecamatan Gaung Anak Serka Kabupaten Indragiri Hilir - Shorea Khaswarina; Muhammad Radix Mahardhika; Evy Maharani (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Sago is the primary source of income for the community in Gaung Anak Serka Subdistrict. However, sago cultivation still faces various challenges, such as a lack of government involvement, suboptimal crop maintenance, small plot sizes, and declining yields. The objective of this study is to assess the sustainability status of sago farming in Gaung Anak Serka Subdistrict and to identify sensitive attributes. The research method employed was a survey conducted in the two largest sago-producing villages in Gaung Anak Serka Subdistrict. The research sample consisted of 35 farmers selected using Random sampling. Data were collected through interviews using a questionnaire and analyzed using Multidimensional Scalling (MDS) with the RAP-Sago approach. The analysis results indicate that the sustainability index is 42,25, which falls into the “Less Sustainable” category. The social dimension has an index value of 33.38, the ecological dimension 44.35, and the economic dimension 49.02. Therefore, it comprehensively fall into the “Less Sustainable” category. Then this study found 9 sensitive attributes influence the sustainability status. This study recommends the formation and strengthening of farmer groups, improving sago farmers’ knowledge, processing and utilizing waste, and expanding the area of sago plantations to enhance sago sustainability in Gaung Anak Serka Subdistrict.